The Women's Study for the Alleviation of Vasomotor Symptoms (WAVS): a randomized, controlled trial of a plant-based diet and whole soybeans for postmenopausal women. Issue 10 (October 2021) - Barnard, Neal D.; Kahleova, Hana; Holtz, Danielle N.; del Aguila, Fabiola; Neola, Maggie; Crosby, Lelia M.; Holubkov, Richard
Abstract: Objective: This study aimed to assess the effects of the combination of a low-fat plant-based diet and soybeans on the frequency and severity of menopausal hot flashes. Methods: Postmenopausal women ( n  = 38) reporting two or more hot flashes/day were randomly assigned to a low-fat, vegan diet, including ½ cup (86 g) of cooked soybeans daily, or to no diet changes for 12 weeks. Frequency and severity of hot flashes were recorded using a mobile application, and vasomotor, psychosocial, physical, and sexual symptoms were assessed using the Menopause-Specific Quality of Life Questionnaire. Significance was assessed using t -tests (continuous outcomes) and chi-squared/McNemar tests (binary outcomes). Results: Total hot flashes decreased 79% in the intervention group ( P  < 0.001) and 49% in the control group ( P  = 0.002; between-group P  = 0.01). Moderate-to-severe hot flashes decreased 84% in the intervention group ( P  < 0.001) and 42% in the control group P  = 0.009; between-group P  = 0.01). From 0 to 12 weeks, 59% (10/17) of intervention-group participants reported becoming free of moderate and severe hot flashes ( P  = 0.002). There was no change in this variable in the control group (between-group P  < 0.001). The Menopause-Specific Quality of Life Questionnaire revealed significantly greater reductions in the intervention group in vasomotor ( P  < 0.0001), psychosocial ( P  = 0.04), physical ( P  < 0.002), and sexual ( P  = 0.01) domains. Conclusions: The combination of a low-fat, vegan diet and whole soybeans was associated with reduced frequency and severity of hot flashes and improved quality of life in vasomotor, psychosocial, physical, and sexual domains in postmenopausal women. During the 12-week study period, the majority of intervention-group participants became free of moderate-to-severe hot flashes. N/A: Video Summary: http://links.lww.com/MENO/A785 . Abstract : Supplemental Digital Content is available in the text